Facilitating Improvements in Interprofessional Pain Management - Carol J Clark (Journal of Novel Physiotherapy and Physical Rehabilitation - Peertechz Publications, 2014)
Pain is a global phenomenon in which it has been estimated that 20% of adults and 8% of children suffer from at any one time of whom 10% suffer chronic pain [1,2]. Pain is the leading reason for primary care consultations (80%) and musculoskeletal pain is the commonest reason for work absenteeism [3,4]. Pain is complex and there are aspects that require better recognition and understanding in order to improve its treatment and management.